The Relationship between Caffeine Consumption and Sleep Quality of Students of the Faculty of Sports Science Universitas Negeri Malang - Rachmawati, Windi Chusniah; Mawarni, Dian; Alma, Lucky Radita; Rahma, Adiska (citeus, 2025)
Coffee is a popular drink consumed in Indonesia, especially among people aged 17 until 25 years. Coffee contains thousands of natural chemicals, one of which is caffeine, which has negative impacts on health if consumed in excessive amounts. The purpose of this study is to describe the caffeine-based beverages consumed and sleep quality and to assess the association between caffeine use and sleep quality. This study used a cross-sectional design with 120 respondents who completed a questionnaire about the history of caffeine-based beverage consumption and PSQI sleep quality, PSQI is used to measure the state of sleep which consists of seven parts: subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency, sleep disturbances, sleep medication, and waking dysfunction. There is a significant correlation (p-value less than 0.05) between the level of caffeine beverage consumption and students' sleep quality. The higher the caffeine consumption category, the greater the risk of having poor sleep quality. It is suggested to implement health promotion strategies, such as educating about consumption limits and the side effects of coffee through various social media platforms to reduce the negative impacts of coffee consumption. Thus, the health of individuals in the productive age group can be maximized.